Improved plug–play SV with virtual inertia for enhancing the stability of high RES‐penetrated grids. Issue 4 (14th August 2019) - Elshenawy, Mahmoud Awad; Abdelkader, Sobhy Mohamed; Amin, Abdelrahman Ahmed; Farghal, Soliman Ahmed
Abstract : The synchronverter (SV) is currently one of the most promising grid‐friendly inverters that mimic synchronous generators (SGs). Almost all the available SV use virtual current signal for synchronization, which require a complicated controller that lacks plug–play capability. This paper proposes a new generation of self‐synchronised SV with a simpler controller, which provides plug–play capability with no need for switching between actual controller current and a virtual current for each ON–OFF process. The proposed SV (PSV) can also share the load with other SGs and SVs and also it is able to take part in regulating system frequency and voltage. A linearised small‐signal model is derived for the controller to investigate its stability. The PSV is also validated through multiple simulation studies carried out in MATLAB/Simulink environment. The results show the capability of the PSV to achieve self‐synchronisation and plug–play operation without a dedicated PLL or a virtual current. Compared to the current self‐synchronised SV, the PSV guarantees a smoother grid connection and gives more accurate reactive power sharing. Moreover, the PSV is applied to a modified IEEE 14‐bus test system considering three different contingencies to prove its impact on enhancing system dynamics and stability.